Keterlibatan Serikat Pekerja Dalam Perubahan Kebijakan Pengupahan Melalui AdvokasiI Sosial - Lestari, Zeni Tri; Wibowo, Arif (Jurnal Ilmu Kesejahteraan Sosial, 2023)
This research is about the involvement of trade unions in changing wage policies through social advocacy from the social welfare perspective. The urgency of conducting this research is to reveal how KASBI's involvement as a worker's union encourages changes in wage policies to ensure better labor welfare through advocacy against the Job Creation Law and advocacy against Minister of Manpower Regulation Number 2 of 2022. This research uses a descriptive qualitative method. Data were collected from February to June 2023 through online and offline interviews involving three informants selected by the purposive sampling technique. The research results reveal that KASBI engages politically to fight for the interests of the labor group, including obtaining guarantees for basic needs. The advocacy process involves planning a strike, consolidating alliances, holding a National Coordination Meeting (Rakornas), conducting a judicial review of the Constitutional Court, holding mass demonstrations, submitting hearings, asking the government for access to draft laws, and writing studies. Supporting factors of involvement and advocacy are credibility and financial independence. Meanwhile, the obstructing factor is the incapability of the governments to openness to the aspirations and interests of the labor group. This research has benefits and contributions to the study of social welfare, especially social welfare in the industrial sector, social policy, and social legislation. The results of this research can be a reference for social workers in carrying out advocacy in the policy realm, as well as a reflection for stakeholders in formulating policies that better accomodate worker’s aspirations.